2011
DOI: 10.1007/s10530-011-0019-6
|View full text |Cite
|
Sign up to set email alerts
|

Island biogeography extends to small-scale habitats: low competitor density and richness on islands may drive trait variation in nonnative plants

Abstract: Previous island biogeography studies have quantified species richness on the scale of entire islands rather than smaller scales relevant to plant-toplant competitive interactions. Further, they have not accounted for density compensation. Using mainland and island sites along the New England coast, we asked two questions. First, are both richness and density lower in small-scale habitats within islands than in similar mainland habitats? Second, do differences in competitor richness and density drive postestabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Classical works suggested that islands tend to be more heavily invaded than their mainland counterparts (Elton 1958;Lonsdale 1999;Pyšek and Richardson 2006). However, other studies confirm our findings supporting that communities in non-oceanic islands tend to be less invaded by non-native plants than in the mainland (Teo et al 2003;Atwood and Meyerson 2011). Furthermore, even when islands were found to be more invaded these differences could be explained by other factors not directly linked to insularity, but to differences in anthropic disturbances (Yiming et al 2006).…”
Section: Discussionsupporting
confidence: 70%
“…Classical works suggested that islands tend to be more heavily invaded than their mainland counterparts (Elton 1958;Lonsdale 1999;Pyšek and Richardson 2006). However, other studies confirm our findings supporting that communities in non-oceanic islands tend to be less invaded by non-native plants than in the mainland (Teo et al 2003;Atwood and Meyerson 2011). Furthermore, even when islands were found to be more invaded these differences could be explained by other factors not directly linked to insularity, but to differences in anthropic disturbances (Yiming et al 2006).…”
Section: Discussionsupporting
confidence: 70%
“…Islands are among the areas most threatened by the success of invasive plants (Denslow et al, 2009;Atwood & Meyerson, 2011). Current literature relates alien success in islands to several variables linked to humans, such as population density (Atwood & Meyerson, 2011;Traveset et al, 2014), the level of human impact (MacDonald et al, 1991;Monty et al, 2013), ecological traits such as genetic diversity (Hardman et al, 2012;Traveset et al, 2014), differences in phylogeny with native species (Bezeng et al, 2013), island area (Traveset et al, 2014), isolation and distance to the nearest continent (Traveset et al, 2014) and climate change (Yamashita et al, 2000). The possible relationship between bedrock K 2O concentrations and alien plant success remains mostly unexplored.…”
Section: K and The Success Of Plant Invasionmentioning
confidence: 99%
“…Greenhouse and growth chamber experiments have shown that competition against A. syriaca , Canada goldenrod ( Solidago canadensis L.), and quackgrass [ Elymus repens (L.) Gould] can substantially reduce Vincetoxicum performance (Blanchard et al 2010; Jackson and Amatangelo 2021; Milbrath et al 2019a; Sanderson and Antunes 2013). Research on V. nigrum has demonstrated that competitive responses are shaped by competitive environments over evolutionary time (Atwood and Meyerson 2011). Competitive environments also matter at smaller, more ecological spatiotemporal scales: in general, plant community invasibility depends on numerous determinants of resource supply and demand (Davis et al 2000).…”
Section: Dispersal and Establishmentmentioning
confidence: 99%